Perbedaan Waktu Pemberian Jawaban dan Hasil Tes Inteligensi Ditinjau dari Perbedaan Lembar Jawaban - Ridwan Saptoto (Jurnal Psikologi, 2012)
Many intelligence test administered designed as paper and pencil test. But efficiency demand in this time make it administered using computer answer sheet, and testie forced to give answer by blackening answer dots using 2B computer pencil in answer sheet. This method reduce testie time to think the right answer, and may influence intelligence test result. This study aimed to compare time to fill answer sheet and intelligence test results, between testie who did test with paper and pencil answer sheet and testie who did test with computer answer sheet. Experiment method choseed in this study. Simple design with repeated sample used in first experiment step. Prior, subjects were assigned to fill answer sheet by streak. And then they assigned to give answer by blackening answer dots. Data analysis show that there were significant difference between first and second assignment (F = 192.192, p < 0.05). Two independent group design used in the second experiment step. Subjects were randomly assigned to join control group or experiment group. Subjects in control group did test using paper and pencil answer sheet, while subjects in experiment group did test using computer answer sheet. Data analysis show that there were significant difference in intelligence level between control group and experiment group in CFIT A (t = 1.681, p < 0.05; one tailed), CFIT B (t = 2.289, p < 0.05; one tailed), and CFIT A and B (t = 1.819, p < 0.05; one tailed). Control group consistently higher in intelligence test results than experiment group. Keywords: intelligence test, CFIT, computer answer sheet